The culture of engineering education and its interaction with gender : a case study of a New Zealand University - Godfrey, Janett Elizabeth (Curtin University, 2003)
This study focused on the culture of engineering education, a culture which has been characterised internationally as reflecting masculine attitudes, values and norms of behaviour, thereby reinforcing the current under-representation of women. The goal of the study was to define the dimensions of the culture and the associated processes of enculturation, highlighting the interaction of these with gender. Following a review of relevant literature, research questions were formulated. These were addressed through an interpretive case study undertaken at a multidisciplinary School of Engineering in a New Zealand university. The study used predominantly ethnographic methods of data collection. To guide the analysis, a model was developed based on Schein's (1985) theoretical framework. The first level of the model involved the identification of observable manifestations of the culture (grouped as Artefacts, Practices and Behaviours). At the second level, shared values and cultural norms were induced from the observable manifestations. At the third level, the essence of the engineering education culture was distilled from these values and norms, in the form of seven cultural dimensions. At each level of the analysis the explicit and tacit processes of enculturation, especially in relation to gender, were considered. This research exposed the masculinity of the basic beliefs and assumptions at the core of the disciplinary culture, revealing the source of enduring cultural norms and their manifestations in behaviours and practices. Diverse forms of masculinity were evident, especially within sub-disciplinary subcultures, but all were constructed in opposition to perceptions of femininity. Participants in the study (whether male, female, students or staff) perceived women in engineering as different, not only to men, but to other women.The women students appeared to construct for themselves a dual identity. They selectively incorporated in this identity both stereotypically masculine and stereotypically feminine qualities, in accordance with their perceptions of simultaneously "doing woman" and "doing engineer". The theoretical significance of this study lies in its provision of an accessible framework for cultural analysis by engineering educators and equity advocates. The framework facilitates exposure of the source of observable behaviours and practices in the unconsciously held beliefs and assumptions at the core of the culture of an institution or discipline. The practical significance lies in its potential to provide a base for developing strategies for cultural change advantageous to the participation of women. The findings of this thesis strongly suggest that such strategies must focus on disrupting the current dualities in language and discourse which implicitly construct women as different, deficient and therefore disadvantaged in engineering education. In particular strategies need to expose behaviours and practices to critical reflection by staff and students, making explicit the values and assumptions which underpin them. Further, while maintaining those features which are the strength of engineering education, there is a need to also include and value ways of knowing and learning styles from outside the current disciplinary and gendered boundaries.